EFFECT OF NPK FERTILIZER DOSAGES ON SOME NEW VARIETIES OF RICE PLANT (Oryza saliva L.) - DARYANTI DARYANTI; TYAS SUMARAH KURNIA DEWI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2009)
The research was done in KelurahanKaumanKidul, KecamatanSidorejo, Kota Salatiga, from February until June 2008, the type of soil is Latosol, the altitude is 525 metere above sea level. This research was arranged in Split-plot Design. Kinds of varieties as main plot concisted of 3 levels: Pepe, Sintanur and IR 64, and dosages of NPK fertilizer as sub plot consisted 4 levels: 0 kg/ha, 200 kg/ha, 250 kg/ha and 300 kg/ha. In this research Urea fertilizer was still used 200 kg/ha. The datas were analyzed using analysis variance and Least Signiï¬cant Difference Qf5% level. The research showed that kinds of varieties inï¬‚uenced signiï¬cant to high of plant, total amount of bough, amount of productive bough, dry shel of rice plant, dry shel of rice milled weight per sample, but not significant to weight of fresh straw anddry straw, dry shel of rice weight per plot, and weight of 1000 seeds. Dosages of NPKfertilizer inï¬‚uenced signiï¬cant to high of plant, total amount of bough, weight of freshand dry straw, weight of dry shell per sample and per plot, weight of dry rice milled persample and per plot and weight of 1000 seeds. Combined effect from two treatmentswas signiï¬cant to weight of dry shell milled per sample and per plot, and not signiï¬cantto other parameters. The highest yield from this research is 6,417 ton/hc fromtreatment IR 64 variety and 300 kg/ha dosage NPK fertilizer, but statistically not signiï¬cant different from treatment with Sintanur or Pepe varieties and dosage fertilizeris 250 kg/ha. From economics analysis knows that using sintanur and Pepe varietieswith dosage fertilizer 250 kg/ha is more proï¬t than IR 64. Key words: rice plant, varieties, NPK dosages Â